Metformin Administration During Early Postnatal Life Rescues Autistic-Like Behaviors in the BTBR T+ Itpr3tf/J Mouse Model of Autism - Wang, Lian; Cai, Yulong; Fan, Xiaotang (Frontiers in Behavioral Neuroscience, 2018)
Autism spectrum disorder (ASD) is a neurodevelopmental disability characterized by impaired social interactions, stereotypical repetitive behavior and restricted interests. Although the global incidence of ASD has increased over time, the etiology of ASD is poorly understood, and there is no effective pharmacological intervention for treating ASD. Recent studies have suggested that metformin has the potential to treat ASD. Thus, in this study, we assessed the therapeutic effects of early metformin treatment in a BTBR T+ Itpr3tf/J (BTBR) mouse model of ASD. We observed that early metformin administration significantly reversed social approach deficits, attenuated repetitive grooming and reduced marble burying in BTBR mice. Metformin did not change the general locomotor activity or anxiety-like behavior in both BTBR and C57BL/6J (B6) mice. Our findings suggest that early metformin treatment may have beneficial effects on ameliorating behavioral deficits in ASD.